Characteristics of Aphasia in Ischemic Stroke Patients at a National Brain Center in Indonesia - Danardhono, Rasya Hapsari; Saleh, Arman Yurisaldi; Theresa, Ria Maria; Astari, Riezky Valentina (Folia Medica Indonesiana, 2023)
Highlights: 1. This study was the first study identifying the characteristics of aphasia among ischemic stroke patients during COVID-19 pandemic at a national brain center in Indonesia. 2. This study provides additional data for future studies to conduct a comparison between the pre- and post-pandemic incidence of aphasia. Abstract Different types of aphasia may occur due to lesions in various brain regions following ischemic strokes. Global aphasia was the most prevalent type of aphasia before the COVID-19 pandemic. However, stroke incidence and mortality rose during the pandemic. This study aimed to identify the types, clinical and radiological features, and management of aphasia in ischemic stroke cases during the pandemic. This study was a descriptive study with a cross-sectional design. The total sampling technique was used for the sampling process. The research samples were ischemic stroke subjects with aphasia who were diagnosed between January 1 and December 31, 2021, at the National Brain Center Prof. Dr. dr. Mahar Mardjono Hospital, Jakarta, Indonesia. The statistical analysis was performed using IBM SPSS Statistics for Mac, Version 25.0 (IBM Corp., Armonk, N.Y., USA). The results of this study showed that 162 aphasic subjects had suffered from ischemic strokes. The age range of the subjects was 34–87 years old. The majority of the subjects were male (59.9%) and aged 55–65 years (37.0%). The three most common risk factors were hypertension (90.1%), diabetes mellitus (50.0%), and dyslipidemia (75.9%). Motor aphasia (33.3%) and global aphasia (43.8%) were the most prevalent types of aphasia among the subjects. The parietal lobe was the main location of the causative lesions, as demonstrated by 38 global aphasic subjects and 47 motor aphasic subjects. The therapies administered to the subjects consisted of speech therapy (85.2%), antiplatelet therapy (98.1%), anticoagulants (19.1%), recombinant tissue plasminogen activator (rTPA) (1.2%), and neuroprotectors (3.0%). This study concluded that global aphasia was the most common type of aphasia among ischemic stroke patients during the pandemic, with the parietal lobe as the primary location of the causative lesions.